Rapid antigen detection test for respiratory syncytial virus diagnosis as a diagnostic tool - Flávio da Silva Mesquita; Danielle Bruna Leal de Oliveira; Daniela Crema; Célia Miranda Nunes Pinez; Thaís Cristina Colmanetti; Luciano Matsumia Thomazelli; Alfredo Elias Gilio; Sandra Elisabeth Vieira; Marina Baquerizo Martinez; Viviane Fongaro Botosso; Edison Luiz Durigon (Elsevier, 2017)
Objective: The aim of this study was to evaluate the QuickVue® RSV Test Kit (QUIDEL Corp, CA, USA) as a screening tool for respiratory syncytial virus in children with acute respiratory disease in comparison with the indirect immunofluorescence assay as gold standard. In Brazil, rapid antigen detection tests for respiratory syncytial virus are not routinely utilized as a diagnostic tool, except for the diagnosis of dengue and influenza. Methods: The authors retrospectively analyzed 486 nasopharyngeal aspirate samples from children under age 5 with acute respiratory infection, between December 2013 and August 2014, the samples were analyzed by indirect immunofluorescence assay and QuickVue® RSV Test kit. Samples with discordant results were analyzed by real time PCR and nucleotide sequencing. Results: From 313 positive samples by immunofluorescence assays, 282 (90%) were also positive by the rapid antigen detection test, two were positive only by rapid antigen detection test, 33 were positive only by immunofluorescence assays, and 171 were positive by both methods. The 35 samples with discordant results were analyzed by real time PCR; the two samples positive only by rapid antigen detection test and the five positive only by immunofluorescence assays were also positive by real time PCR. There was no relation between the negativity by QuickVue® RSV Test and viral load or specific strain. The QuickVue® RSV Test showed sensitivity of 90%, specificity of 98.8%, predictive positive value of 99.3%, and negative predictive value of 94.6%, with accuracy of 93.2% and agreement κ index of 0.85 in comparison to immunofluorescence assay. Conclusions: This study demonstrated that the QuickVue® RSV Test Kit can be effective in early detection of Respiratory syncytial virus in nasopharyngeal aspirate and is reliable for use as a diagnostic tool in pediatrics. Resumo: Objetivo: Avaliar o teste QuickVue® RSV Test Kit (QUIDEL Corp, CA, EUA) para o diagnóstico rápido do vírus sincicial respiratório em crianças com doença respiratória aguda, comparando-o com a imunofluorescência indireta como padrão ouro. Visto que, no Brasil, testes rápidos para detecção de antígenos para vírus sincicial respiratório não são rotineiramente utilizados como ferramenta de diagnóstico, exceto para Dengue e Influenza. Métodos: Um total de 486 amostras de aspirado de nasofaringe de crianças menores de 5 anos com doença respiratória aguda, coletadas entre dezembro de 2013 e agosto de 2014, foram analisadas por imunofluorescência e pelo teste QuickVue®. Amostras com resultados discordantes entre os métodos foram submetidas a PCR em tempo real e sequenciamento. Resultados: Das 313 amostras positivas por IFI, 282 foram positivas no teste rápido (90%), 2 amostras foram positivas apenas no teste rápido (0.6%), 33 apenas na imunofluorescência (10.5%) e 171 foram negativas em ambos os métodos. As 35 amostras com resultados discordantes foram testadas por PCR em tempo real, sendo que duas que foram positivas apenas no teste rápido e 5 apenas na imunofluorescência confirmaram-se positivas. Não houve relação entre a ausência de positividade no teste QuickVue® com a carga ou com a cepa viral. O teste QuickVue® mostrou sensibilidade de 90.1%, especificidade 98.9%, valor preditivo positivo 99.3%, valor preditivo negativo de 94.6%, acurácia de 93.2% e índice κ de concordância de 0.85 em comparação à imunofluorescência. Conclusões: Nosso estudo demonstrou que o teste QuickVue® RSV pode ser efetivo na detecção precoce do vírus sincicial respiratório em amostras de aspirado de nasofaringe e é confiável como uma ferramenta de diagnósticos em pediatria. Keywords: Respiratory viruses, Respiratory syncytial virus - RSV, Rapid antigen detection test - RADT, Palavras-chave: Viroses Respiratórias, Virus Sincicial Respiratório - VSR, Teste Rápido de Detecção de Antígeno - TRDA